Jurassic world - Trevorrow, Colin; Marshall, Frank; Crowley, Patrick; Universal Studios; Amblin Entertainment (California : Universal Studios, 2014)
22 years ago, John Hammond envisioned a theme park where guests could experience the thrill of witnessing actual dinosaurs. Today, Jurassic World welcomes tens of thousands of visitors, but something sinister lurks behind the park's attractions: a genetically modified dinosaur with savage capabilities. When chaos erupts across the island, Owen and Claire race to restore order as a day in the park becomes a struggle for survival.
Based on characters created by Michael Crichton.
Special features: Deleted scenes ; Chris & Colin take one the'World'.
Executive producers, Steven Spielberg, Thomas Tull ; director of photography, John Schwartzman ; music, Michael Giacchino.
Chris Pratt, Bryce Dallas Howard, Vincent D'Onofrio, Ty Simpkins, Nick Robinson, Omar Sy, BD Wong, Irfan Khan.
DVD format, Aspect ratio (2.00:1), Region 3, Dolby Digital.
In English, Brazilian Portuguese, Latin American Spanish & Thai with optional English, Bahasa Indonesia, Brazilian Portuguese, Cantonese, Korean, Latin American Spanish, Thai & Traditional Chinese subtitles.
Keywords: Dinosaurs in motion pictures; Dinosaurs -- Drama